Filming fiction : Tagore, Premchand and Roy - Asaduddin, M.; Ghosh, Anuradha (Oxford University Press, 2012)
Papers presented at a seminar on Fiction into film : Satyajit Ray's interpretation of Tagore and Premchand, held at Jamia Millia Islamia during 23-25 November 2006.